Tidal modulation of ice-shelf flow: a viscous model of the Ross Ice Shelf. Issue 221 (2014) - Brunt, Kelly M.; MacAyeal, Douglas R.
Abstract: Three stations near the calving front of the Ross Ice Shelf, Antarctica, recorded GPS data through a full spring–neap tidal cycle in November 2005. The data revealed a diurnal horizontal motion that varied both along and transverse to the long-term average velocity direction, similar to tidal signals observed in other ice shelves and ice streams. Based on its periodicity, it was hypothesized that the signal represents a flow response of the Ross Ice Shelf to the diurnal tides of the Ross Sea. To assess the influence of the tide on the ice-shelf motion, two hypotheses were developed. The first addressed the direct response of the ice shelf to tidal forcing, such as forces due to sea-surface slopes or forces due to sub-ice-shelf currents. The second involved the indirect response of ice-shelf flow to the tidal signals observed in the ice streams that source the ice shelf. A finite-element model, based on viscous creep flow, was developed to test these hypotheses, but succeeded only in falsifying both hypotheses, i.e. showing that direct tidal effects produce too small a response, and indirect tidal effects produce a response that is not smooth in time. This nullification suggests that a combination of viscous and elastic deformation is required to explain the observations.